Greater sage‐grouse male lek counts relative to a wind energy development - Chad W. Lebeau; Jeffrey L. Beck; Gregory D. Johnson; Ryan M. Nielson; Matthew J. Holloran; Kenneth G. Gerow; Trent L. McDonald (Wildlife Society Bulletin)
ABSTRACT Wind energy development is an emerging source of anthropogenic disturbance that could affect greater sage‐grouse (Centrocercus urophasianus; sage‐grouse) populations. Our objective was to determine the response of male sage‐grouse attending leks (lek counts) to wind energy development using a before/after–control/treatment study design. We counted males attending each lek within control and treatment areas annually and analyzed peak numbers. We obtained lek count data from 5 treatment and 9 control leks over an 11‐year period. We estimated trends in lek counts pre‐ (2006–2008) and postdevelopment (2009–2016) using a generalized linear mixed negative binomial model. We considered time lags at which the effect of the wind energy development was realized by the male breeding population. Although all lek counts were apparently in decline prior to development and trends on the control and treatment area changed during postdevelopment, we found no negative differences in the relative trends in lek counts between control and treatment areas between pre‐ and postdevelopment periods. We detected a 56% drop in lek counts at treatment leks relative to control leks assuming the effect of the wind energy development was realized between 2010 and 2011 (i.e., 3 yr postdevelopment). Use of a posteriori power analysis estimated similar data sets would have 80% probability of detecting a 28% decrease in the rate of decline of lek counts at treatment leks relative to control leks after development. Our findings suggest males attending leks in close proximity to wind energy development may respond differently compared with leks in close proximity to other forms of anthropogenic features, adding to a growing body of literature regarding the potential effects of energy development on prairie grouse. We recommend additional research and an abundance of caution in designating buffer sizes <1.5 km to avoid measurable effects from wind energy development on males attending leks. © 2017 The Wildlife Society.